Henri VIII (1491-1547) - Hackett, Francis, 1883-1962 (Paris : Payot, 1934)
Son adolescence - Henri et Catherine - Anne Boleyn - Jane Saymour - Anne de Clèves - Catherine Howard - Catherine Parr
Keywords: Hendrik VIII [Koning van Engeland].